Unravelling the enigmatic ISM conditions in Minkowski's object. Issue 4 (12th October 2020) - Zovaro, Henry R M; Sharp, Robert; Nesvadba, Nicole P H; Kewley, Lisa; Sutherland, Ralph; Taylor, Philip; Groves, Brent; Wagner, Alexander Y; Mukherjee, Dipanjan; Bicknell, Geoffrey V
ABSTRACT: Local examples of jet-induced star formation lend valuable insight into its significance in galaxy evolution and can provide important observational constraints for theoretical models of positive feedback. Using optical integral field spectroscopy, we present an analysis of the ISM conditions in Minkowski's object ( z = 0.0189), a peculiar star-forming dwarf galaxy located in the path of a radio jet from the galaxy NGC 541. Full spectral fitting with ppxf indicates that Minkowski's object primarily consists of a young stellar population \! 10 Myr old, confirming that the bulk of the object's stellar mass formed during a recent jet interaction. Minkowski's object exhibits line ratios largely consistent with star formation, although there is evidence for a low level (\! 15 per cent ) of contamination from a non-stellar ionizing source. Strong-line diagnostics reveal a significant variation in the gas-phase metallicity within the object, with (O / H ) + 12 varying by \! 0.5 dex, which cannot be explained by in-situ star formation, an enriched outflow from the jet, or enrichment of gas in the stellar bridge between NGC 541 and NGC 545/547. We hypothesize that Minkowski's object either (i) was formed as a result of jet-induced star formation in pre-existing gas clumps in the stellar bridge, or (ii) is a gas-rich dwarf galaxy that is experiencing an elevation in its star formation rate due to a jet interaction, and will eventually redden and fade, becoming an ultradiffuse galaxy as it is processed by the cluster.